Maritime Academy Planning High School Essay Contest - Vallejo Times-Herald (Vallejo Times-Herald)
The California Maritime Academy will conduct an essay contest for senior class public school boys in the Bay Area with ocean voyages as prizes for winners, it was announced yesterday. Commo. Russell M. Ihrig, USN (ret.), academy superintendent, said the essay contest will be on the subject, "The American Merchant Marine for World Trade and World Peace." Entries must be 1,000 words or less.